What Makes Indian Management Students Thrive? Role of Decision-Making Discretion, Broad Information Sharing, and Climate of Trust - Chhajer, Raina; Chaudhry, Smita (Frontiers in Psychology, 2022)
Thriving is a psychological state in which individuals experience a sense of vitality and a sense of learning. Thriving come from relational connections with others, and is deeply rooted in social systems. Theoretical literature suggests that thriving occurs in the presence of decision-making discretion, broad information sharing, and a climate of trust. However, no study has investigated these environmental factors empirically. Using a multiple-studies approach, we (a) established valid and reliable scale for each of these environmental factors using experimental vignettes, (b) confirmed the association of decision-making discretion, broad information sharing and climate of trust with thriving, and (c) identified the role of self-determination theory in determining these relationships. Our analysis was based on data collected from 512 Indian management students across five studies. The results indicate significant difference in thriving for high vs low level for decision-making discretion, broad information sharing and climate of trust. The relationship of these environmental factors with thriving is mainly due to the fulfilment of the need for competence. Competence partially mediates the relationship of decision-making discretion with thriving, and fully mediates the relationship of broad information sharing and climate of trust with thriving. Autonomy, although positively related with the environmental factors, does not lead to thriving. Practical implications, limitations and research avenues are discussed.